Discovery of a new blue quasar: SDSS J022218.03–062511.1. Issue 6 (July 2015) - Fix, M. B.; Smith, J. A.; Tucker, D. L.; Wester, W.; Annis, J.
Abstract We report the discovery of a bright blue quasar: SDSS J022218.03–062511.1. This object was discovered spectroscopically while searching for hot white dwarfs that may be used as calibration sources for large sky surveys such as the Dark Energy Survey or the Large Synoptic Survey Telescope project. We present the calibrated spectrum, spectral line shifts and report a redshift of z = 0.521±0.0015 and a rest‐frame g‐band luminosity of 8.71×1011 L⊙. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)